Where Copyright Law and Technology Once Again Cross Paths: The Continuing Saga: RecordTV Pte Ltd v MediaCorp TV Singapore Pte Ltd [2011] 1 SLR 830 - SAW, Cheng Lim (Institutional Knowledge at Singapore Management University, 2011)
This article critically analyses the issues and reasoning behind the recent Singapore Court of Appeal decision in RecordTV Pte Ltd v Mediacorp TV Singapore Pte Ltd on the legality of digital copying and communications technology under Singapore’s copyright law and offers a different perspective (and some alternative arguments) on the three issues of copying, communication to the public and authorisation of copyright infringement. In particular, we will identify the relevant party to these acts and examine their definitions, based on the current statutory provisions and the history of the development of copyright law vis-à-vis modern technology.